2012
DOI: 10.1016/j.rppneu.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of dysphagia and palpitation caused by the compression exerted by an enormous mediastinal lipoma

Abstract: A 65-year-old woman presented with mild dysphagia, weight loss and intermittent palpitation. Chest radiograph revealed a large opacity in the right lower lung field. Subsequent CT scan showed a large posterior mediastinal lipoma extending from the level of the aortic arch to the thoracoabdominal junction. After thoracoscopic resection, the patient's dysphagia and palpitation were resolved. After a follow-up of 2 years, the patient has had no evidence of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Uni-port, single-port and single-incisional thoracoscopic surgery have all suggested that there are a number of procedures that can be performed using only a single small wound. Currently, from primary spontensous pneumothorax to lung cancer resection, thoracoscopic surgery using single-port approach has been shown to be feasible [2,4-7]. Taking advantage of the various modifications endoscopic techniques, we can now perform nearly all such procedures without the need of either curved instruments or additional port wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uni-port, single-port and single-incisional thoracoscopic surgery have all suggested that there are a number of procedures that can be performed using only a single small wound. Currently, from primary spontensous pneumothorax to lung cancer resection, thoracoscopic surgery using single-port approach has been shown to be feasible [2,4-7]. Taking advantage of the various modifications endoscopic techniques, we can now perform nearly all such procedures without the need of either curved instruments or additional port wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the pliancy of the lung tissues, the wound can be very small [4,5]. Currently, the wound size depends on the overall size of the three instruments, including a 10-mm stapler, a 5-mm endoscope and a 5-mm grasp, as shown in Figure 1B.…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques had been proposed in the treatment of lung cancer, mediastinal tumor, pneumothorax and most common disease of the chest. [1][2][3][4][5] With modifications of conventional thoracoscopic techniques, the operative field can be extended to the contralateral side of the pleural space. In the case we presented, peel formation and loculations were mainly located in right side pleural space while the left side effusion was relatively free-floating.…”
Section: Commentmentioning
confidence: 99%
“…Single-port approach, when operated with experienced surgeon's hands, is much faster than conventional multiport approach and has low conversion rate as we reported earlier. 2,3,5) When treating malignant pleural effusion, mediastinal metastasis may occur if the mediastinum is opened. Therefore, the adequacy of such procedure in treating malignant effusion is still not clear.…”
Section: Commentmentioning
confidence: 99%
“…According to our limited experience, the final size of the port wound in single-port VATS depends on the solid portion of the neoplasm (Figure 8) rather than the overall size. For large but very soft tissues, such as normal lung tissue or a specimen of primary spontaneous pneumothorax, they can be easily and gently retracted out into the endo-bag through a tiny wound [5]. The solid part, however, cannot be altered by pressure, as deformation may lead to confusion on the part of the pathologist upon microscopic examination.…”
Section: Case Presentationmentioning
confidence: 99%